Common variant rs356182 near SNCA defines a Parkinson's disease endophenotype. Issue 1 (25th November 2016) - Cooper, Christine A.; Jain, Nimansha; Gallagher, Michael D.; Weintraub, Daniel; Xie, Sharon X.; Berlyand, Yosef; Espay, Alberto J.; Quinn, Joseph; Edwards, Karen L.; Montine, Thomas; Van Deerlin, Vivianna M.; Trojanowski, John; et al.
Abstract: Objective: Parkinson's disease (PD) presents clinically with several motor subtypes that exhibit variable treatment response and prognosis. Here, we investigated genetic variants for their potential association with PD motor phenotype and progression. Methods: We screened 10 SNPs, previously associated with PD risk, for association with tremor‐dominant (TD) versus postural‐instability gait disorder (PIGD) motor subtypes. SNPs that correlated with the TD/PIGD ratio in a discovery cohort of 251 PD patients were then evaluated in a multi‐site replication cohort of 559 PD patients. SNPs associated with motor phenotype in both cross‐sectional cohorts were next evaluated for association with (1) rates of motor progression in a longitudinal subgroup of 230 PD patients and (2) brain alpha‐synuclein ( SNCA ) expression in the GTEx (Genotype‐Tissue Expression project) consortium database. Results: Genotype at rs356182, near SNCA, correlated with the TD/PIGD ratio in both the discovery (Bonferroni‐corrected P = 0.04) and replication cohorts ( P = 0.02). The rs356182 GG genotype was associated with a more tremor‐predominant phenotype and predicted a slower rate of motor progression (1‐point difference in annual rate of UPDRS‐III motor score change, P = 0.01). The rs356182 genotype was associated with SNCA expression in the cerebellum ( P = 0.005). Interpretation: Our study demonstrates that the GG genotype at rs356182 provides molecular definition for a clinically important endophenotype associated with (1) more tremor‐predominant motor phenomenology, (2) slower rates of motor progression, and (3) decreased brain expression of SNCA . Such molecularly defined endophenotyping in PD may benefit both clinical trial design and tailoring of clinical care as we enter the era of precision medicine.